Prejudice, Political Ideology, and Interest: Understanding Attitudes Toward Affirmative Action in Brazil. Issue 3 (6th August 2021) - Turgeon, Mathieu; Habel, Philip
Abstract : Few public policies have been as consequential or divisive as affirmative action. Proponents have argued for the need for equity and the redress of past and present discrimination, whereas opponents enlist claims over individual liberty and merit. Scholars have examined support to affirmative action, asking to what extent citizens' support is shaped by their political ideology, interest, prejudice, or some combination thereof. Much work to date has focused on the United States, where disentangling theoretical explanations has proved challenging. We turn our attention to an understudied but important case: Brazil. Brazil has implemented a broad form of affirmative action for admission to federal universities that include consideration of the applicant's education, income, and race. Adopting both a conventional question and a list experiment embedded in a face‐to‐face survey among a nationally representative sample of adult Brazilians, we find that public support for affirmative action suffers from social desirability bias, and in our subsequent regression analysis, that attitudes about affirmative action are structured especially by individuals' interests.